Effect of famotidine on oesophageal sensitivity in gastro-oesophageal reflux disease. Issue 4 (April 1994) - Marrero, J M; de Caestecker, J S; Maxwell, J D
Abstract : Gastric acid suppression could improve heartburn by healing oesophagitis or by reduction of oesophageal sensitivity to acid. To independently assess changes in oesophageal sensitivity, it would be necessary to study patients with reflux disease but no oesophagitis. The aim of this study was to investigate the effect of acid suppression on oesophageal sensitivity and to assess the time course of any measured effect. Twenty seven patients were recruited, of whom 25 completed the study (14 men and 11 women, mean (SD) age 50 (15) years). All had classic symptoms of gastro-oesophageal reflux but normal results of upper gastrointestinal endoscopy and oesophageal mucosal histological tests. Each had abnormal 24 hour pH studies and a positive acid perfusion tests. Subjects were assigned double blind to placebo (n = 11) or famotidine 40 mg twice daily (n = 14) for four weeks. Acid perfusion tests were carried out at 0, 4, 5, and 8 weeks and time to heartburn recorded. Time to heartburn (mean (SEM)) was 124 (78) seconds in the famotidine and 187 (154) in the placebo group at week 0 (NS). Compared with baseline, significant increases in time to heartburn was found with famotidine at weeks 4 (383 (102), p < 0.01) and 5 (344 (92), p < 0.01) but not week 8 (336 (90) seconds). No significant effects were found with placebo (219 (41), 146 (23), and 144 (25) seconds for weeks 4, 5, and 8). Heartburn symptom score decreased significantly with famotidine (mean scores 3.6, 1.9, 2.1, and 2.6 at weeks 0, 4, 5, and 8 (p=0.001)) and showed a significant negative correlation with time to heartburn (r(s)=-0.60; p<0.0001). It is concluded that oesophageal sensitivity to acid is reduced by famotidine independent of and effect on oesophagitis; the effect wanes one to four weeks after the end of treatment and correlates with change in heartburn score.